ANALISIS BEBAN KERJA DAN KOMPENSASI TERHADAP KINERJA PEGAWAI KANTOR DESA SUNGAI BAKAU KECIL KABUPATEN MEMPAWAH - Siti Nurdiana; Farhil Husaini (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This study aims to analyze the effect of workload and compensation on the performance of employees of the village office of Sungai Bakau Kecil, mempawah district. The method of analysis used in this research is a qualitative method using a descriptive approach. The data collection techniques used are interviews and observations. The results showed that excessive workload caused by a lack of assertiveness from village leaders in enforcing work standards and unstable compensation caused a decrease in employee performance. For this reason, the village needs to increase assertiveness in employee supervision and management, consistent enforcement of rules, transparency in the distribution of tasks, and attention to employee welfare. Providing fair rewards and appropriate compensation will help improve employee motivation and performance, and create a more productive and harmonious work environment. Keywords: Workload, Compensation and Employee Performance